So each may learn: integrating learning styles and multiple intelligences - Silver, Harvey F.; Strong, Richard W.; Perini, Matthew J. (Alexandria, Va. Association for Supervision and Curriculum Development, 2000)
One of the greatest challenges faced by every school and every educator is encouraging and accommodating a full range of student diversity while simultaneously promoting a uniformly high level of academic achievement for all students. Two powerful learning models -- multiple intelligences and learning styles -- provide us with the best means of rising to this challenge. Yet each model has particular strengths and weaknesses that directly correspond to the strengths and weaknesses of the other, meaning that a truly holistic model -- one that allows educators to engage a full range of human diversity and meet rigorous academic standards -- occurs only in the integration of these two great models."--Page 4 of cover.
Includes bibliographical references
Keywords: Learning, Psychology; Multiple intelligences; Cognitive styles